Chemistry for engineers - Yen, Teh Fu, 1927-2010. (Singapore ; London : Imperial College Press, 2019)
"This book aims at bridging the concepts and theory of chemistry with examples from fields of practical application, thus reinforcing the connection between science and engineering. It deals with the basic principles of various branches of chemistry, namely, physical chemistry, inorganic chemistry, organic chemistry, analytical chemistry, surface chemistry, biochemistry, geochemistry, fuel chemistry, polymer chemistry, cement chemistry, materials chemistry, and asphalt chemistry. Written primarily for use as a textbook for a university-level course, the topics covered here provide the fundamental tools necessary for an accomplished engineer."--Publisher's website.
Physical chemistry -- Inorganic chemistry -- Organic chemistry -- Analytical chemistry -- Surface chemistry -- Biochemistry -- Geochemistry -- Fuel chemistry -- Polymer chemistry -- Cement chemistry -- Materials chemistry -- Asphalt chemistry.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Includes bibliographical references and index.
Keywords: Chemistry; Chemical engineering; Electronic books